Employee Productivity: Analysis of Job Satisfaction and Work Engagement in Industry Shipping Line - Primadi Candra Susanto; Ni Nyoman Sawitri; Hapzi Ali; Zahara Tussoleha Rony (MultiTech Publisher, 2023)
The purpose of this paper is to analyze work engagement, job satisfaction, and employee productivity in the shipping industry, and provide practical guidance to companies in this sector to improve performance. This research uses quantitative methods with data analysis techniques using SPSS 24 to find the influence between variables and simultaneously. The object of research is shipping companies with a sample of 43 employees, by random sampling The Job Satisfaction variable has a positive effect on the Employee Productivity variable, the Work Engagement variable has no effect on Employee Productivity, and simultaneously the Job Satisfaction (X1), and Work Engagement (X2) variables simultaneously have a positive effect on Employee Productivity (Y). These results represent the results in the shipping field. The contribution of the results of this study can be used as a reference for other researchers in the future.